PENGARUH SUHU KEMPA DAN KONSENTRASI PEREKAT SERBUK CANGKANG KEPITING TERHADAP SIFAT FISIKA DAN MEKANIKA PAPAN PARTIKEL LIMBAH SERBUK GERGAJI KAYU MAHONI - , MUHAMMAD MUSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The human need for wood is increasing, but the amount of wood supply is decreasing and it is exacerbated by the production of wood-processing waste in large quantities. The processing and the utilization of wood waste are expected to be able to solve these issues, such as the creation of artificial board products, i.e. particle boards. Generally, particle boards use synthetic adhesives that are less environmentally friendly and renewable, thus it, is necessary to find other alternatives to solve this problem , which are the chitosan-based adhesives that are derived from crab shell wastes. The main ingredient of this research is mahogany saw dust waste s and the natureal adhesive of crabs shell powders. The factors used are the adhesive concentration of 10%, 20%, and 30% and the compression temperature of 160oC and 180oC. This particleboard manufacturing refers to the process of particleboard manufacturing standards. The testing products include physical properties (moisture content, density, thickness development, and water absorption) and mechanical properties (internal bonding strength, modulus of fracture, and modulus of elasticity) based on the Japanese Industrial S tandard for particleboards (JIS A 5908 Type-8). The best properties of the mahogany w ood saw dust waste particleboards were obtained from the treatment of 20% adhesive concentration and the compression temperature of 160oC, where only the values of the moisture content and the density meet the standards of JIS A 5908 Type-8, w ith a value of water content of 8,282%, density of 0,711 g/cm3, the thickness swelling of 94,692%, water absorption of 192,065%, internal bonding strength of 0,760 kg/cm2, modulus of elasticity of 4845,164 kgf/cm2, and modulus of rufture of 18,710 kgf/cm2.